Gen Z's Interest in Online Travel Agencies in Indonesia: A Modified UTAUT2 - Jevin Leon; Fredian Simanjuntak; Muhamad Dody Firmansyah (G-Tech: Jurnal Teknologi Terapan, 2025)
The rapid evolution of digital technology has transformed the travel and tourism industry, making Online Travel Agencies (OTAs) a preferred medium for trip planning and booking. OTAs offer seamless access to flights, accommodations, and other travel services, catering to Indonesia's mobile-first population and digitally savvy Gen Z users. This study examines factors influencing behavioral intention (BI) and use behavior (UB) toward OTAs, extending the UTAUT2 model with trust, website quality, and AI integration. Data from 300 respondents were analyzed using Structural Equation Modeling (SEM) via SPSS and AMOS. Results show that performance expectancy, effort expectancy, social influence, hedonic motivation, price value, trust, website quality, and AI integration positively affect BI. Habit negatively influenced BI, while BI, facilitating conditions, and habit positively impacted UB. These findings highlight the need for OTA providers to align user expectations with actual experiences, enhancing satisfaction and long-term adoption among Gen Z users.